How variation in internet access, digital skills, and media use are related to rural student outcomes: GPA, SAT, and educational aspirations. (October 2021) - Hampton, Keith N.; Robertson, Craig T.; Fernandez, Laleah; Shin, Inyoung; Bauer, Johannes M.
Highlights: Broadband access fills the "homework gap" but has little relationship to GPA. Social media skills are related to higher performance on standardized exams (SAT). Cell phone dependence for home Internet is related to lower digital skills. Benefits of social media skills outweigh any negative influences of excessive use. Internet access, use, and skills have limited influence on educational aspirations. Abstract: Some have pointed to divides in the availability of fixed home broadband Internet access as a contributor to rural students' lower levels of educational attainment. Based on standardized exams (SAT Suite) and a survey of rural Michigan students in grades 8–11, we find that rural students with broadband home Internet access are more interested in school and leave homework incomplete less often. However, the relationship to classroom grades (GPA) is relatively trivial. Yet, we find that students who are not dependent on a cell phone for Internet access and those with higher digital skills, especially social media skills, rank considerably higher on the SAT. Rural students with broadband Internet access are able to participate in a more diverse array of online media activities, which supports building digital skills. Any negative relationship between time spent on social media, video games, other digital media and educational outcomes is outweighed by the benefit to digital skills. However, aspects of rural culture; including the emphasis on activities such as sports, as a path to postsecondary schooling and upward, social mobility; may be stunting the positive relationship between access, digital skills, and educational aspirations. Whereas extra-curricular sports have no direct relationship to SAT performance, students who spend more time on sports receive higher grades and have higher educational aspirations than those with more digital skills. We discuss the implications for rural students' access to human capital and how the unequal relationship between digital skills and performance in the classroom and on the SAT may perpetuate inequalities.